Characterizations of Hemirings Based on Probability Spaces - Bin Yu; Jianming Zhan (Journal of Applied Mathematics)
The notion of falling fuzzy h-ideals of a hemiring is introduced on the basis of the theory of falling shadows and fuzzy sets. Then the relations between fuzzy h-ideals and falling fuzzy h-ideals are described. In particular, by means of falling fuzzy h-ideals, the charac-terizations of h-hemiregular hemirings are investigated based on independent (prefect positive correlation) probability spaces.